EFFECTIVENESS OF STABILITY BALL EXERCISES COMBINES WITH ERGONOMIC SETTING IN PREGNANCY RELATED LOW BACK PAIN. A RANDOMIZED CONTROL TRIAL - Anam Aftab; Amjad Rashed Hamdan Alyahyawi; Sara Kafeel; Nabeela Kanwal; Javeria shehzadi; Hadia Nadeem; Rizwana Butt (The Rehabilitation Journal, 2021)
Background: Pregnancy related low back pain (PR-LBP) is very common, which affects activities of daily life including work, sleep, physical activity and compromise the quality of life. The prevention PR-LBP through physical therapy is uncommon in Pakistani population. Objective: to determine the effectiveness of stability ball exercises (SBE) in combination with ergonomic training (ET) in pregnancy related low back pain (PR-LBP). Methodology: A single blinded, randomized clinical trial was conducted at physical therapy department of Haleema Siraj Hospital Rawalpindi Pakistan. A total of n=90, who were coming to the clinic for follow-up, fulfilled the inclusion criteria and were thus recruited through non-probability convenient sampling technique. The study participants were randomly divided in to two groups i.e. SBE (n=45) and combination of SBE with ES (n=45), through lottery method. Quebec disability scale (QDS) was used to determine the functional disability. Results: The mean age of study participants was 26.5±4.56723 years. Significant improvement was observed in both groups with larger effect size throughout the treatment duration (p<0.05).Conclusion: SBE and combination of SBE with ES significantly reduced low back pain and functional disability